Proteomics and disease network associations evaluation of environmentally relevant Bisphenol A concentrations in a human 3D neural stem cell model - Horánszky, Alex; Shashikadze, Bachuki; Elkhateib, Radwa; Lombardo, Salvo Danilo; Lamberto, Federica; Zana, Melinda; Menche, Jörg; Fröhlich, Thomas; Dinnyés, András (Frontiers in Cell and Developmental Biology, 2023)
AH prepared the experimental design, performed cell culturing, BPA treatments, spheroid size analysis, RT-qPCR, immunocytochemistry, viability assays, cellROX assays, Mitotracker assays, data analysis and interpretation, and drafted the manuscript. FL performed data interpretation, manuscript reviewing and editing. BS & RE performed LC-MS/MS and data analysis. SDL performed network analysis and interpretation. MZ supervised the experimental design, data analysis, results interpretation, and manuscript writing. AD designed the research project, contributed to the interpretation of results and final revision of the manuscript. TF & JM participated in the interpretation of results, and manuscript revision. All authors read and approved the final version of the manuscript.